REVISION DE LOS GENEROS DIPLODISCUS DIESING 1836 Y MEGALODISCUS CHANDLER 1923 TREMATODA PARAMPHISTOMOIDEA I - HOLLIS BRAVO, MARGARITA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
Historical data are given as to the systematic position of the genera Diplodiscus and Megalodiscus; an attempt is made at the unification in the terms used in the description of the species Johnston, 1913); D amphichrus Tubangui, 1933 ( = D sinicus Li,
ANS INST BIOL
Keywords: REVISION, GENEROS DIPLODISCUS DIESING, 1836, MEGALODISCUS CHANDLER, 1923, TREMATODA: PARAMPHISTOMOIDEA I; CIENCIAS DE LA VIDA; MICROBIOLOGIA; BACTERIOLOGIA